Pembekalan Kewirausahaan Tenaga Kerja Mandiri (TKM) Bidang Pertanian - Evi Rosalina Widyayanti; Insiatiningsih (Jurnal Pengabdian Masyarakat Akademisi, 2022)
The Covid-19 pandemic that has hit the entire world has shattered the order of human life before. This condition is a big challenge for all countries in the world in order to survive in times of crisis due to the outbreak of this disease. The impacts include various sectors of human life, including the impact of the decline in the community's economy due to the pandemic, many companies have had to close their businesses and lay off their employees by termination of employment. For employees who experience termination of employment, it will be very difficult to live the next life. Therefore, it is important for them to immediately find a way out to be able to still have an income for their family. The government through the Manpower and Transmigration Office pays attention to workers affected by the Covid-19 pandemic as victims of this termination of employment by providing Self Employment Entrepreneurship Debriefing in the Agricultural Sector, namely Hydroponic Entrepreneurship Training. Hydroponics that produces vegetables and also fisheries through even narrow land and the use of small amounts of water capacity is very helpful in producing a promising business. The results of hydroponic vegetables are expected to be easily traded and traded because they are products of everyday people's needs, with easy and cheap raw materials. Keywords: Covid-19 Pandemic, Hydroponics, Entrepreneurial Termination